Experimental validation of positioning and tracking system using ultra-wideband and low-cost microcontroller units - Ngoc-Son Duong; Minh-Tuyen Vu; Minh-Duc Nguyen; Thai-Mai Dinh Thi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
Indoor positioning systems (IPS) have become increasingly critical in various applications, from asset tracking to smart environments. While global positioning system (GPS) offers precise outdoor localization, its signal is unavailable indoors. Ultra-wideband (UWB) technology emerges as a promising alternative due to its high accuracy, robustness against multipath interference, and ability to operate in dense environments. Aiming to develop an affordable and efficient system, we present a UWB-based IPS using the DW1000 UWB chip, evaluated with two different low-cost microcontroller units (MCUs): the ESP8266 system-on-chip (SoC) and the Arduino Uno R3. The findings suggest that the ESP8266 SoC is a superior choice for building an affordable and efficient UWB IPS, making it a compelling option for widespread adoption in budget-sensitive applications.